2018
DOI: 10.1016/j.athoracsur.2017.11.060
|View full text |Cite
|
Sign up to set email alerts
|

A Pragmatic Preoperative Prediction Score for Nonhome Discharge After Cardiac Operations

Abstract: We identified preoperative risk factors for NHD after cardiac operations and developed a pragmatic NHD prediction score with high accuracy. Addition of postoperative risk factors for NHD only modestly improved prediction. NHD does not decrease the readmission rate after cardiac operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Another important observation in our study, is that women had higher rate of nonhome discharge compared with men (11.3% vs 6.9%, p < .01). These findings concur with other studies, which showed that female sex has high association with nonhome discharge after TAVR and cardiac surgeries 25,26 …”
Section: Discussionsupporting
confidence: 93%
“…Another important observation in our study, is that women had higher rate of nonhome discharge compared with men (11.3% vs 6.9%, p < .01). These findings concur with other studies, which showed that female sex has high association with nonhome discharge after TAVR and cardiac surgeries 25,26 …”
Section: Discussionsupporting
confidence: 93%
“…The unexpected nature of EGS limits opportunities for preoperative optimization, leading to high rates of non‐home discharge, months away from home even after discharge, and high rates of hospital encounters, particularly in patients with frailty. Although preoperative prediction models have been proposed to identify patients at high risk for non‐home discharge after surgery, these models do not include frailty assessments and were largely developed for patients undergoing elective surgery . Including frailty screens during the EGS hospitalization can have two benefits.…”
Section: Discussionmentioning
confidence: 99%
“…16 Based on prior studies, primary outcome was discharge destination, defined as home or NHD. 2,8 NHD included a rehabilitation facility, skilled nursing facility, nursing home, or long-term acute care facility and was abstracted via chart review.…”
Section: Variables and Outcomesmentioning
confidence: 99%
“…However, risk scores and machine-learning algorithms designed to predict length of stay and discharge destination are not always optimized for ease of use at the point of care. 8 Professional societies including the American Geriatrics Society and American College of Surgeons (ACS) recommended using frailty screens for older adults admitted for surgery to prompt interdisciplinary care teams to effectively preserve functional independence, decrease delirium, and reduce 30-day readmission risk in their admitted patients. 4,[9][10][11] However, less is known about the use of frailty screens in a preoperative setting to predict postdischarge needs.…”
mentioning
confidence: 99%